2013
DOI: 10.2320/matertrans.mh201318
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Pressure Torsion to WC–Co Ceramic-Based Composites for Improvement of Consolidation, Microstructure and Hardness

Abstract: This study shows that ultrafine-grained composites of WC11 mass% Co are successfully consolidated by high-pressure torsion (HPT) followed by sintering at lower sintering temperatures or shorter sintering time than hot isostatic pressing (HIP) and compression and sintering. For the samples processed by HPT and successive sintering, the grain size (³700 nm) is smaller and the hardness (³1700 Hv) is higher when compared to those consolidated by compression and sintering and HIP. A heterogeneous microstructure con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…After compression, the lower HPT anvil is rotated against the upper anvil under pressure and large shear strain is induced in the material ( γ = 2 πrN / h ; γ : shear strain; r : radial distance from disc center, N : number of HPT turns, h : thickness of disc). The high pressure in this method significantly suppresses the failure of material and provides a unique condition to process hard and/or brittle materials such as high‐melting‐temperature metals, intermetallics, glasses, ceramics, silicon, carbon polymorphs, and polymers …”
Section: Introductionmentioning
confidence: 99%
“…After compression, the lower HPT anvil is rotated against the upper anvil under pressure and large shear strain is induced in the material ( γ = 2 πrN / h ; γ : shear strain; r : radial distance from disc center, N : number of HPT turns, h : thickness of disc). The high pressure in this method significantly suppresses the failure of material and provides a unique condition to process hard and/or brittle materials such as high‐melting‐temperature metals, intermetallics, glasses, ceramics, silicon, carbon polymorphs, and polymers …”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the earlier reports on the improvement of consolidation of ceramics by HPT processing. [32,33] Figure 5(c) shows that the sintered samples exhibit similar dielectric loss, especially at temperatures in the range of 70-140°C. Therefore, the increase in dielectric constant is not due to the effect of dielectric loss.…”
mentioning
confidence: 98%
“…[32,33] Earlier papers reported that the optimum grain size to achieve high dielectric constants was in the range of 700-1,300 nm. [2,3,5] However, this present work suggests that the optimum grain size can shift even to the nanometer level after severe straining.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is applicable to hard and less ductile materials [5,6] even to intermetallics [7][8][9], ceramics [10][11][12][13], and semiconductors [14][15][16][17]. The samples for the HPT are used in the form of disk or ring and [18,19], because the shear strain is introduced in proportion to the distance from the rotation center [1], the ring sample is preferable to achieve a homogeneous structure throughout the sample [18,19].…”
Section: Introductionmentioning
confidence: 99%